Social Support as a Catalyst for Environmental Awareness in Indonesia - Naufal, Ahmad; Laili, Nurfi (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Environmental awareness is crucial for communities to preserve ecosystems and prevent environmental degradation. Social support can play a significant role in fostering this awareness. Specific Background: In rural communities like Tutur village, Pasuruan regency, environmental awareness and social support are often interconnected. However, the extent to which social support influences environmental awareness remains underexplored. Knowledge Gap: While studies have examined environmental education and awareness, few have investigated the role of social support as a driving factor in increasing environmental responsibility in village settings. Aims: This study aims to examine the influence of social support on environmental awareness among the residents of Tutur village, focusing on the relationship between these variables using quantitative methods. Results: The findings from simple linear regression analysis reveal that social support has a significant effect on environmental awareness, indicating that residents with stronger social ties exhibit higher levels of concern and action toward environmental preservation. Novelty: This study offers a novel insight by quantitatively demonstrating the direct relationship between social support and environmental awareness in rural communities, highlighting social dynamics as a key factor in environmental education. Implications: The results suggest that enhancing social support networks through community-driven initiatives can significantly improve environmental consciousness and foster sustainable tourism development, particularly in rural areas like Tutur village. This study provides a basis for future research on integrating social support frameworks into environmental sustainability strategies, particularly in regions with strong communal ties. Highlights: Social support boosts environmental awareness in community residents. Strong community ties enhance responsibility for environmental preservation. Findings promote initiatives to improve environmental consciousness and tourism. Keywords: environmental awareness, social support, Tutur village, quantitative research, sustainability